Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1111/j.1442-2026.1994.tb00512.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of anterior shoulder dislocation by external rotation

Abstract: Objective: To examine the efficacy of external rotation as initial treatment for anterior shoulder dislocation. Design: Prospective uncontrolled study of the efficacy and adverse effects of external rotation when used as the initial technique to reduce anterior shoulder dislocation. Results: Ninety two cases of anterior shoulder dislocation were treated over an 18 month period. External rotation was used successfully to reduce the dislocation in 72 cases (78%). A further nine cases were reduced by external … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
(8 reference statements)
1
1
0
Order By: Relevance
“…Our study demonstrated that the external rotation method is easy to perform and able to achieve a closed reduction of an acute anterior dislocation or fracturedislocation of the shoulder in 96% of the patients. Our success rate is similar to that reported by Mirick, 7 Eachempati, 8 George Tseng, 13 Danzl DF 14 and colleagues.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study demonstrated that the external rotation method is easy to perform and able to achieve a closed reduction of an acute anterior dislocation or fracturedislocation of the shoulder in 96% of the patients. Our success rate is similar to that reported by Mirick, 7 Eachempati, 8 George Tseng, 13 Danzl DF 14 and colleagues.…”
Section: Discussionsupporting
confidence: 90%
“…Eachempati and colleagues 8 reported successful reduction in 36 patients among 40 patients (90%). George Tseng and colleagues 13 showed 78% success rate in their 92 cases of anterior shoulder dislocation treated with external rotation method as the initial technique and they recommended as the initial technique for anterior shoulder dislocations. Danzl DF and colleagues 14 reported the successful reduction in 78 of 100 consecutive patients presented with anterior shoulder dislocations.…”
Section: Discussionmentioning
confidence: 99%